Reviewed book: Dalia STREIMIKIENE (2026), Circular Economy Assessment Indicators and Applications, Routledge, 442 p. - Griesienė, Ingrida (Transformations In Business & Economics, 2026)
Reviewer: Dr. Ingrida Griesienė, associated professor at Vilnius University